Mobile Augmented Reality for Campus Visualization Using Markerless Tracking in an Indonesian Private University - Arifitama, Budi; Hanan, Ghali; Rofiqi, Muhammad Halim (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Marker in augmented reality plays a major part to initiate a virtual object in an augmented environment. Choosing a correct and reliable marker would increase the chance of creating a more stable augmented object especially for visualizing a building structure. Unfortunately, most research on visualizing building structure uses a marker-based tracking approach where users must always bring a pre-printed paper as a tracking media. This creates a problem for every time users demonstrate a specific augmented structure object, they still need to bring a printed marker to show the augmented object. The purpose of this research is to investigate the applicability of markerless-based tracking as a solution whether it can substitute the marker-based tracking on augmented reality problems. Simultaneous Localization and Mapping (SLAM) is used as a markerless tracking method where it tracked and mapped the surface environment using feature extraction, then set an anchor at the specified location where the augmented object visualization appears. The results of the research found that from a total of 30 object detection tests, 21 objects are successfully detected and 9 undetected objects, this shows that markerless-based tracking is applicable and can substitute marker-based tracking for a structural campus visualization.